A Non-Volatile Tunable Ultra-Compact Silicon Photonic Logic Gate - Peng, Zheng; Feng, Junbo; Yuan, Huan; Cheng, Wei; Wang, Yan; Ren, Xiaodong; Cheng, Hao; Zang, Shengyin; Shuai, Yubei; Liu, Hao; Wu, Jiagui; Yang, Junbo (Nanomaterials (Basel, Switzerland), 2022)
Logic gates, as one of the most important basic units in electronic integrated circuits (EICs), are also equally important in photonic integrated circuits (PICs). In this study, we proposed a non-volatile, ultra-compact all-photonics logic gate. The footprint is only 2 μm × 2 μm. We regulate the phase change of optical phase change materials(O-PCMs) Sb2Se3 to switch the function of the logic gate. The Sb2Se3 possess a unique non-volatile optical phase change function; therefore, when Sb2Se3 is in the crystalline or amorphous state, our device can work as XOR gate or AND gate, and our designed logic ‘1’ and logic ‘0’ contrasts reach 11.8 dB and 5.7 dB at 1550 nm, respectively. Compared with other traditional optical logic gates, our device simultaneously has non-volatile characteristics, tunability, and additionally an ultra-small size. These results could fully meet the needs of fusion between PICs and EICs, and developing truly chip-scale optoelectronic logic solution.